2012
DOI: 10.1289/ehp.1104432
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Lipophilic Environmental Chemicals and Endometriosis: The ENDO Study

Abstract: Background: An equivocal literature exists regarding the relation between persistent organochlorine pollutants (POPs) and endometriosis in women, with differences attributed to methodologies.Objectives: We assessed the association between POPs and the odds of an endometriosis diagnosis and the consistency of findings by biological medium and study cohort.Methods: Using a matched cohort design, we assembled an operative cohort of women 18–44 years of age undergoing laparoscopy or laparotomy at 14 participating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 53 publications
4
44
0
5
Order By: Relevance
“…Maternal and paternal age were highly correlated (r ¼ 0.73), which precluded the inclusion of paternal age into the model. We did not include parity in our model because its adjustment can induce overadjustment bias (34).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal and paternal age were highly correlated (r ¼ 0.73), which precluded the inclusion of paternal age into the model. We did not include parity in our model because its adjustment can induce overadjustment bias (34).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study assessed the association between POPs and the odds of an endometriosis diagnosis and the consistency of findings by biological medium and study cohort. 58 Using a matched cohort design, it was shown that cohort-specific and biological-medium-specific POPs were associated with endometriosis, underscoring the importance of methodological considerations when interpreting findings.…”
Section: Recommendationmentioning
confidence: 99%
“…Seemingly ubiquitous, endocrine disruptors are present in industrial solvents and lubricants [polychlorinated biphenyls (PCBs), polybrominated biphenyls (PBBs), dioxins], pesticides [methoxychlor, chlorpyrifos, dichlorodiphenyltrichloroethane (DDT)], fungicides (vinclozolin), pharmaceutical agents [diethylstilbestrol (DES)] and flame retardants [polybrominated diphenyl ethers (PBDEs)] [25,26]. A wealth of evidence links exposures to EDCs with causation or exacerbation of endometriosis [25,27-33]. For example, pre-natal exposure of mice to bis-phenol A (BPA) results in female offspring with an endometriosis-like condition [30,32].…”
Section: Introductionmentioning
confidence: 99%
“…After adjusting for serum lipid levels, gravidity, and tobacco use, four PCB congeners, which are anti-estrogens, imparted a three-fold risk of developing endometriosis in a cohort of 84 women [28]. Furthermore, an evaluation of persistent organic pollutants (POPs) in omental fat (OF) and serum collected from women diagnosed with endometriosis revealed a significant positive association between α-hexachlorocyclohexane levels and endometriosis [33]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation